Color Change, Phenotypic Plasticity, and Camouflage - Stevens, Martin (Frontiers in Ecology and Evolution, 2016)
The ability to change appearance over a range of timescales is widespread in nature, existing in many invertebrate and vertebrate groups. This can include color change occurring in seconds, minutes, and hours, to longer term changes associated with phenotypic plasticity and development. A major function is for camouflage against predators because color change and plasticity enables animals to match their surroundings and potentially reduce the risk of predation. Recently, we published findings (Stevens et al. 2014a) showing how shore crabs can change their appearance and better match the background to predator vision in the short term. This, coupled with a number of past studies, emphasizes the potential that animals have to modify their appearance for camouflage. However, the majority of studies on camouflage and color plasticity have focused on a small number of species capable of unusually rapid changes. There are many broad questions that remain about the nature, mechanisms, evolution, and adaptive value of color change and plasticity for concealment. Here, I discuss past work and outline six questions relating to color change and plasticity, as well as major avenues for future work.